4 DEKADE HUKUM PERKAWINAN DI INDONESIA: MENELISIK PROBLEMATIKA HUKUM DALAM PERKAWINAN DI ERA MODERNISASI - Aristoni Aristoni (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2016)
The come up of Marriage Law No. 1 1974 on Marriage and KHI (Compilation of Islamic Law) is the demands and as the answers to all the unrest and uncertainty faced by the Muslim community to be the foundation and or references in overcoming problems related tofamily law. A bill of the Law on modern marriage is a form of response to pressure from women's organizations at the time, and greatly this ordinance establishes rules of monogamy and gave equal rights to divorce for women and men although the ordinance only applied to people who choose the rules of registration of marriage. Article 1 of Law No. 1 Year 1974 on Marriage, which meant that the marriage is aphysical and spiritual bond between a man and a woman as husband and wife, having the purpose of establishing a happy and lasting family founded on the Belief in God Almighty. From the conception ofreligious law and the country has actually oriented to human welfare. However, the law is no more than the normative rules that govern people's behavior patterns, the number of legal issues facing society,especially in matters of marriage, then the marriage law required to provide answers to these problems. Therefore, the law should evolve according to the changing times so that can accommodate the growingvalues in society, including in this case the value of their customs, traditions and religion. The law should also not be closed to the renewal effort that suits your needs and benefit together. Ideally, the law should uphold Islamic principles and values of human rightsamong them welfare.